Produção e qualidade de mini tomate em sistema orgânico, dois tipos de condução de hastes e poda apical - Takahashi, Keiko [UNESP] (2014)
Tomato is, probably, the vegetable species with the highest number in paper published. However, with the continuous release of new cultivars the need of research also becomes constant. Nevertheless, despite the great importance of cultural practices on tomato yield, there is still lack of research on mini tomato cultivation. Therefore, the present study was conducted to evaluate the effect of top pruning and stem conduction of grafted mini tomato plants, cultivated in organic system, on yield and fruit quality. The experimental design used was the completely randomized blocks, with four treatments, 16 replications and six plants per plot. Treatments were resultant from factorial 2 x 2, with two stem conduction types (secondary stem conducted immediately under the first cluster of main stem, named as traditional conduction; or stems conducted from axillary buds of the two leaves immediately above the grafting point, named as “bottom” stem conduction) and two number of leaves between the top pruning and the last cluster (three or five leaves). Stems conduction type influenced in most of the characteristics evaluated, being that when two “bottom” stems were conducted, results were superior for total and marketable production, clusters number, total fruit number, marketable fruit number and utilization percentage, when comparing to treatments in which the traditional stem conduction used by tomato growers were utilized. Leaves number left between top pruning and the last cluster did not influence the characteristics evaluated. Based on the results obtained it is possible to conclude that the conduction of two “bottom” stems was superior to traditional conduction, with larger production of commercial fruits.